Front Matter Vol. 55, No. 3 September (2019) - Matter, Front (Folia Medica Indonesiana, 2019)
This study was conducted to identify the presence of icaA and icaD genes in S. epidermidis and to analyze the relationship between the presence of icaA and icaD genes with the ability of in vitro biofilm formation in S. epidermidis. S. epidermidis isolates from patients and healthy people were collected and PCR was examined to detect icaA and icaD genes. which then continued to examine the ability of biofilm formation by the method of Congo Red Agar. The results of this genotypic and phenotypic examination were then tested for correlation with statistical tests using SPSS 23.0. A total of 40 S. epidermidis isolates were collected, consisting of 20 clinical isolates and 20 isolates of normal flora. The icaA gene was positive in 5 isolates (12.5%), and 8 isolates (20%) were positive for the icaD gene, 3 isolates with icaA and icaD were both positive. One hundred percent of isolates with icaA or icaD positively formed biofilms, but there were 15 isolates (42.9%) who did not have the icaA gene but showed the ability to form biofilms, while 12 isolates (37.5%) who did not have the icaD gene also formed biofilms. Fifty percent of S. epidermidis isolates showed the ability to form biofilms at CRA. The Fisher Exact test showed a significant relationship between the icaA gene and the ability of biofilm formation (p=0.047 (p<0.05)) as well as the icaD gene (p=0.03 (p<0.05)). The icaA and icaD genes have a significant relationship to biofilm formation in S. epidermidis. There was another mechanism in the formation of biofilms that are not dependent on the ica gene.